EARLY AND LATE SYNCHROGRANITIZATIONAL BLASTOMYLONITES IN PERVOMAISKA FAULT ZONE - Mazko, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper explores stages in granitization of the leucocratic blastomylonites intersected by melanocratic tectonites. The study focuses on difeldspar migmatites and gneissoid granites, variegated in texture, structure and composition, which are the tectonites of the Pervomaiska gneissoid granite monocline. The prevalent blastomylonites in the study area are light gray, light pink and pink, average-to-coarse-grained, pegmatoid, porphyroclastic, heavily schistose and banded. Early leucocratic pegmatoid tectonites occur subvertically and are intersected by melanocratic tectonites at 45o. Showing no major recumbency or discontinuity of the directive structures, the intersection provides evidence of a brittle-ductile deformation. Rotational amplitude and vector being vague to define, the juxtaposition of the deformed fragments of the pegmatite vein in the late tectonites is assumed to have been affected by low amplitude of shear or thrust deformational processes, though. The hypothesis made is further confirmed by the occurrence of Fsp porphyroclasts as well as Fsp quartz aggregates. The thickness of the melanocratic layer observed within 3 m makes 8–10 cm, with an azimuth being 240–260o, and the gradient making 45–55o. This is contrasted to leucocratic tectonites with an 80o azimuth and an 85o gradient. Melanocratic tectonites are of fine-grained texture and Fsp biotite-quartz chemistry. They are identified based on blastomylonite fine-grained granoblastite texture with traces of relict Fsp and garnet porphyroclasts, as well as low mineralized quartz lenses that are similar to those of the basic gneissoid granites. Blastasy is quite mature, while sections reveal distinct blastomylonite schistose features. Minor porphyroclasts can be seen throughout the study area, which suggests permanent hetero-axial brittle-ductile deformation. The leucocratic tectonites being intersected by the melanocratic ones is obvious. What raises further consideration is the temporal correlation between the deformational processes in question and the Palaeo-Proterozoic granitization. Interestingly, microtectonic evidence suggests late and post granitization deformations having been in sync, with granitization strains showing considerable variability.